2012
DOI: 10.1177/0950017011432919
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating in a competitive world: musicians’ working lives and understandings of entrepreneurship

Abstract: Recent interest in ‘creative’ work practices has been brought about by organizational restructuring and the emergence of the creative industries as an economic power. Drawing on research with musicians in the North East of England, this article explores musicians’ understandings of their working lives within the new entrepreneurial agenda. Musicians are shown to be enterprising in pursuing a musical calling in a difficult market and of particular interest is the extent to which they see themselves as entrepren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(181 citation statements)
references
References 37 publications
9
159
1
12
Order By: Relevance
“…Elsewhere it is argued that the relationships between players in the same friendship groups are characterized by bonds of togetherness and comradery while also showing evidence of tension, conflict, and rivalry. This also corroborates with previous research on friendship networks that has indicated the often 'double edged' nature of relationships between employees, which can be particularly problematic in occupations characterized by short-term placements, low pay, and uncertainty (Coulson, 2012;Umney & Kretsos, 2014).…”
Section: Loneliness Isolation and Work Life Balancesupporting
confidence: 90%
“…Elsewhere it is argued that the relationships between players in the same friendship groups are characterized by bonds of togetherness and comradery while also showing evidence of tension, conflict, and rivalry. This also corroborates with previous research on friendship networks that has indicated the often 'double edged' nature of relationships between employees, which can be particularly problematic in occupations characterized by short-term placements, low pay, and uncertainty (Coulson, 2012;Umney & Kretsos, 2014).…”
Section: Loneliness Isolation and Work Life Balancesupporting
confidence: 90%
“…Coulson 2012;Demazière and Gadea 2009), engaging in a range of work activities across sectors to provide them with different forms of income. Consider, for instance, a professional free-skier sponsored by different companies, working seasonally as a ski instructor and bartender, in addition of writing articles for magazines based on her travels, all the while posting short videos of her skiing on YouTube, photos on Instagram, and updating her profile on Facebook (Thorpe 2014(Thorpe , 2016.…”
Section: The Work Of Action Sport Athletes: From Exploitation To Entrmentioning
confidence: 99%
“…This was also important for achieving a balance in terms of gender and age. These emerged as potentially significant factors in earlier studies, notably those by Coulson (2012), Siebert and Wilson (2013) and Umney and Kretsos (2014) which suggest a link between relative youth and more individualistic, instrumental and careerist propensities. There were similar numbers of male and female respondents, and also an even split between age groups in Northern Ireland, with 7 aged between 20-39 and the same number in the 40-70 age range.…”
Section: Participants and Methodsmentioning
confidence: 92%
“…Economic and egotistical orientations come to dominate, crowding out other possible or likely influences on cultural workers. Yet there is some contrasting empirical research, notably by Coulson (2012) on musicians, which concentrates on the reflexive abilities of artists and the potential, at least for some, to criticise the workings of inhospitable labour markets and adapt, collectively and constructively, devising supportive networks and collaborative learning arrangements, for example. By this assessment, non-instrumental values and the critical faculties of artists remain important, seeming to heighten sensitivity in some cases and counteract attempts to seduce workers or camouflage unpalatable controls.…”
Section: Introductionmentioning
confidence: 99%